Influence of physical exercise on practice standards morphofunctional, immune function and quality of elderly with aids: case study. - Araújo, Ana Paula Serra de; Bertoline, Sônia Maria Marques Gomes; Junior, Joaquim Martins; Bertolini, Dennis Armando; Gouvêa, José Alípio Garcia (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: Acquired Immunodeficiency Syndrome (AIDS) is an infectious disease caused by the human immunodeficiency virus (HIV) that causes progressive immunodeficiency virus, rendering the infected individual susceptible to opportunistic infections and diseases. Your clinical treatment is basically medicine and brings with it a number of side effects among which stands out the development of muscle fatigue, lipodystrophy and decreased quality of life. In order to improve the quality of life of people with AIDS, researchers have investigated what kind of benefits to the practice of activity can bring to these individuals. Objective: To evaluate the influence of physical activity on the morphofunctional supervised patterns, immune function and quality of life of elderly patients with AIDS. Method: A descriptive study in which volunteers participated in 4 elderly women with AIDS, who underwent a program of physical activity lasting 16 weeks. Results: The results showed that the proposed program of physical activity was beneficial to functional morphology patterns, immune function and quality of life in older study participants. Conclusion: Sixteen weeks of exercise intervention targeted to elderly patients with AIDS are beneficial, because they promote improvements in the components of morphofunctional standards, with emphasis on flexibility and muscle strength as well as possible changes in markers of immune function and quality domains of life